Pré-tratamento do bagaço de cana de açúcar com amônia aquosa para a produção de etanol - Silva, Gislene Mota da (Universidade Federal de São Carlos, 2011)
The aim of this work was evaluated the sugarcane bagasse (SCB) pretreatment by aqueous ammonia, an alkaline method. Samples of SCB (in natura and steam exploded unwashed) were pretreated with ammonium hydroxide solution (NH4OH) at 1:5 solid-liquid ratio (by weight), in a bench scale. Preliminary assays were carried out employing NH4OH solution (28% w/w) at room temperature 24 ± 3 ⁰C by 7, 15 and 30 days. In these experiments, it was observed that the pretreatment was selective in removing lignin and hemicellulose. New experiments were carried out using at 50⁰C and NH4OH 15% during 30, 60 and 90 minutes. In these pretreatments the same behavior was observed. In the next assays, it decided to fix the reaction time in 60 minutes and the temperature in 100⁰C. Samples of in nature and steam exploded SCB were pretreated at diffent NH4OH concentrations (4 to 15%). Enzymatic hydrolysis assays were carried out in Erlenmeyers flasks (50⁰C, pH 4.8 and 250 rpm) using 30 FPU/g bagasse (Accellerase 1500, Genencor) and 5 CBU/g bagasse (BG, Genencor). Experiments were carried out employing in natura SCB (pretreated conditions 4, 10 and 15% NH4OH solution, 60 min., 100⁰C) with 3% of solid loading. A glucose conversion of 64.2% was reached in the best condition (10% NH4OH solution). Experiments were carried out employing steam exploded SCB (5, 10 e 15% NH4OH solution, 60 min. and 100⁰C) with 5% of solid loading. A glucose conversion of 79.9% was reached in the best condition (15% NH4OH solution). Hydrolysis experiments using higher solid loading (5% for in natura and 10% for steam exploded) and 30 FPU/g cellulose (Accellerase 1500) were carried out. A glucose conversion of 69.6% for in natura and 82.2% for steam exploded SCB were obtained. Fermentation assays (250 rpm, 30⁰C) employing commercial and industrial Saccharomyces cerevisiae were conducted, in a rich and poor medium. A theoretical fermentation yield up to 78% was found for the poor medium and around 88% for the rich medium. The industrial S. cerevisiae shows a value of yield slightly superior to those of commercial strain. Samples of SCB (before and after pretreatment) were analyzed by scanning electron micrograph (SEM).
Keywords: Engenharia bioquímica; Biomassa; Pré-tratamento alcalino; Amônia aquosa; Hidrólise enzimática; Fermentação alcoólica; Biomass; Alkaline pre-treatment; Aqueous ammonia; Enzymatic hydrolyzes; Alcoholic fermentation; ENGENHARIAS::ENGENHARIA QUIMICA